Structural conditions for relay ramp fault development on the edge of the collision wedge: a case study from the East Slovak Basin - Jacko, Stanislav; Ďuriška, Igor; Janočko, Juraj; Farkašovský, Roman; Thiessen, Alexander Dean (Comptes Rendus. Géoscience)
The Neogene evolution of the Pannonian extensional back-arc basin was associated with the development of transform faults. These faults significantly modified the sedimentary and structural evolution of the basin. The key developmental factors were related to pull forces and to the tilting of the subducted slab. The transitions from upper crustal contraction of upper crustal extension affected the depositional space, which had opened subparallel NW–SE normal faults along the southern contact with the Carpathian collision zone. The entire transition process was controlled by the closing of the rear part of the accretionary space, which changed the dip of the subducted slab. Basin subsidence, which occurred from west to east via N–S steps, generated a system of subparallel-oriented faults, which were connected by relay ramps. The relay ramps had four developmental phases: (a) initial crustal bending, (b) intact ramp formation with structural integrity disturbance, (c) breaching with crustal breakage, and (d) final fault growth. The genesis of the relay ramps of the Eastern Slovak Basin was closely linked to the initial strike-slip movements. The strike-slip movements caused a counterclockwise rotation of the northern edge of the Alpine–Carpathian–Pannonian block. This rotation was later compensated by the tectonic subsidence of the basin, primarily during the Middle Miocene.